Qingfei Dayuan granules and decoction alleviate acute lung injury via TLR4 signaling pathway modulation, gut microbiota regulation, and metabolic reprogramming - Cheng, Huanbo; Ha, Jingwen; Ba, Yuanming (Frontiers in Pharmacology, 2025)
ObjectiveTo explore and compare the therapeutic effects and underlying mechanisms of Qingfei Dayuan Granules (QFDYGs) and Qingfei Dayuan Decoctions (QFDYDs) for the treatment of acute lung injury (ALI), focusing on the modulation of the TLR4 signaling pathway, intestinal microbiota, and related metabolic pathways.MethodsThe active metabolite contents were measured by ultrahigh-performance liquid chromatography. A mouse model of lipopolysaccharide-induced ALI (tracheal instillation) was used to assess efficacy. After drug administration, lung tissue damage was analyzed by hematoxylin-eosin staining and quantification of inflammatory cytokines and oxidative stress biomarkers with enzyme-linked immunosorbent assays. Components of the TLR4 signaling pathway were quantified by Western blot analysis. Intestinal flora regulation was assessed by 16S rRNA sequencing with metabolic pathway analysis via metabolomics. Multivariate statistical methods were applied to analyze differences in gut microbiota and metabolites between groups.ResultsLevels of eight metabolites were 2.44–3.74 times greater following treatment with QFDYGs vs. QFDYDs, although both demonstrated significant protective effects against pulmonary inflammation through TLR4 signaling pathway modulation, gut microbiota restoration, and metabolic regulation. QFDYDs more effectively suppressed production of the pro-inflammatory cytokines TNF-α and IL-1β, while QFDYGs exhibited superior capability to reduce malondialdehyde levels and restore glutathione, catalase, and superoxide dismutase activities. QFDYGs demonstrated greater inhibition of the TLR4-TRIF/MyD88-NF-κB-NLRP3 signaling pathway, whereas QFDYDs more effectively normalized lung injury-induced metabolic changes. Both formulations significantly modulated metabolic pathways, as evidenced by sustained changes to 11 key metabolites, and improved intestinal microbiota composition and functionality.ConclusionBoth QFDYGs and QFDYDs offer protection against ALI. QFDYGs could serve as effective alternatives to QFDYDs, with equivalent or potentially superior therapeutic effects. The choice between QFDYGs and QFDYDs should be guided by specific clinical presentations and therapeutic goals.